Sobre a natureza homogénea do Pretérito Perfeito Composto em Português Europeu - Oliveira, Fátima (2018)
In European Portuguese, 'Pretérito Perfeito Composto' (PPC) is a tense that presents some peculiarities distinguishing it clearly from similar constructions in other languages. Although this construction exhibits a single-eventuality reading in other languages, in EP there is typically a multiple eventuality reading. So, in the first part of this paper, we discuss the quantification over situations underlying the PPC in EP considering the notions of frequency, habituality and iteration. We argue that iteration is the relevant concept, as PPC converts an undetermined number of basic events of the same type into a single event. However, in some cases, the PPC in EP has a second reading available: a single-eventuality, like in other languages. Therefore, in the second part of this paper, we present an aspectual analysis of the PPC that includes both the single-event reading and the iterative reading, in order to provide a unified explanation for both readings. To do so, we will resort to the notion of homogeneity as defined in Landman & Rothstein 2012a e 2012b). We will argue that homogeneity is a central aspectual property of PPC in EP and that the distinction between segmental homogeneity and incremental homogeneity proposed by these authors for 'for x time' adverbials allows us to explain both readings of this EP tense.